Library Environments and Organisations Opportunities or Constraints? - Thomas, Sarah E.. (OECD Publishing, 2003)
The following article is based on a presentation by Sarah E. Thomas, a librarian at Cornell University in the United States. This abridged version begins by summarising how libraries thrive in an era of change. Next it explores storing print publications and how libraries are increasing space for services and activities. The paper then addresses new roles and partners for libraries and, finally, architectural solutions to spatial constraints
Keywords: Education